Peran Kecanduan Smartphone dan Stres Akademik Terhadap Kualitas Tidur pada Mahasiswa - Fazril, Raisya Azzahra; Ulfa, Fara; Widiningsih, Yuli (UIR Press, 2024)
Sleep is a fundamental necessity that must be met by every individual, including students. Poor sleep patterns among students can have significant impacts on both their physical and psychological well-being. Therefore, students must pay attention to their sleep habits to ensure they achieve high-quality rest. Quality sleep refers to a state in which a person experiences restful and restorative sleep, leaving them feeling refreshed and energized upon waking. Factors such as smartphone addiction and academic stress have been shown to affect sleep quality. This study aims to examine the influence of smartphone addiction and academic stress on sleep quality among students at a university in Pekanbaru. The study's participants consisted of 250 students aged between 17 and 24 years, selected through purposive sampling. Data were collected using scales that measured sleep quality, smartphone addiction, and academic stress, and were analyzed using multiple linear regression. The results indicated that both smartphone addiction and academic stress significantly impacted sleep quality (R=0.521; R2=0.271; F=45.92; p<0.01). Achieving good sleep quality is more feasible when smartphone usage is kept in moderation and emotional regulation is well-managed.